Hygienic Quality of Macrotermes (Isoptera, Termitidae) alates (consumed in Lomé Togo) - Mawabena, Kadanga; Boris, Kasseney Dodji; Reine, Dossou Bayi; Tètouwalla, Awili; Mamatchi, Mélila; Essodolom, Paka; Tchadjobo, Tchacondo; Isabelle, Glitho Adolé (Asian Journal of Biological and Life Sciences)
Aim/Background: Macrotermes alates are a source of animal protein for many populations. However, their consumption is not without health risks related to their hygienic quality. This study aims to evaluate the hygienic quality of alates of the genus Macrotermes consumed in Lomé. Materials and Methods: An analysis of some germs was then carried out on traditionally caught and roasted samples. These samples were compared to those obtained by capture with a swabbing net and oven dried at 45°C for 72 hr. The impact of packaging with or without wrapping on the hygienic quality during storage was also assessed. Results: The data obtained showed that the alates samples captured and roasted in the traditional way were highly contaminated with the germs of interest after 7 days of storage. Unpackaged alates were more contaminated (25354333.00 ± 835.00 cfu/g FMAT, 6840.00 ± 92.00 cfu/g TC, 533.33 ± 62.00 cfu/g CF, 313.30 ± 12.99 cfu/g yeast and 46763.00 ± 418,00 cfu/g mould) than the packaged ones (570.00 ± 40.00 cfu/g FMAT, 16.00 ± 03.67 cfu/g TC, 10.00 ± 02.01 cfu/g CF, 07.01 ± 0.99 cfu/g yeast and 16.00 ± 02.00 cfu/g mould). In contrast, the oven dried and packaged alates sample showed only traces of FMAT (02.00 ± 00.10 cfu/g). Conclusion: It appears that the microbiological quality of consumed alates depends not only on the capture and cooking methods, but also on the packaging for preservation. It is therefore necessary to raise awareness of good hygiene practices in the interests of consumer health safety.
Keywords: Food use; Hygienic quality; Macrotermes alates; Togo